AI aided IoT sensor for green building application - Mylsamy Boojha Rukmi (Nanyang Technological University, 2024)
Recently Singapore has been focusing a lot more on being a green city and being sustainable. Green buildings have emerged as a pivotal solution to reduce energy consumption and minimise environmental impact. The integration of Artificial Intelligence (AI) and Internet of Things (IoT) sensors in building management systems have been an integral part in increasing comfort and reducing energy usage, specifically in heating, ventilation and air conditioning (HVAC) systems. The primary objective of this project is to determine which Machine Learning (ML) model and AI guided system would be the best to predict the internal temperature in a room and in the future adjusting air conditioner settings in real time.